The human embryo in vitro : breaking the legal stalemate/ Catriona A. W. McMillan, University of Edinburgh. - McMillan, Catriona A. W. (Cambridge bioethics and law., 2021)
The Human Embryo in vitro explores the ways in which UK law engages with embryonic processes under the Human Fertilisation and Embryology Act 1990 (as amended), the intellectual basis of which has not been reconsidered for almost thirty years. McMillan argues that in regulating 'the embryo' - that is, a processual liminal entity in itself - the law is regulating for uncertainty. This book offers a fuller understanding of how complex biological processes of development and growth can be better aligned with a legal framework that purports to pay respect to the embryo while also allowing its destruction. To do so it employs an anthropological concept, liminality, which is itself concerned with revealing the dynamics of process. The implications of this for contemporary regulation of artificial reproduction are fully explored, and recommendations are offered for international regimes on how they can better align biological reality with social policy and law.